Pengembangan Nontransgenik F1 dan Bc1f1 Padi Ciherang Toleran Genangan secara Site-Directed Crossing - Djarot Sasongko Hami Seno; Satya Nugroho; Tri Joko Santoso; Joel Rivandi Sinaga; Euis Marlina; Dimas Adrianto; Rudi Munzirwan; Aniversari Apriana; Zainal Alim Mas'ud (IPB University, 2014)
The development of submergence tolerant rice varieties is urgently required to maintain the stability of future food production, to anticipate the unpredictable global climate changes. Due to in-economical agronomic traits of native submergence tolerant varieties for large scale cultivation, submergence tolerance gene (sub1) must be introduced into popular high-yielding rice variety, such as Ciherang. To develop new submergence tolerant variety with good agronomic traits as those of Ciherang, in this research, submergence tolerance gene (sub1) was introduced into Ciherang variety. To avoid strict GMO regulation, gene introduction was carried out through site-directed crossing. Donor sub1 was crossed with Ciherang host. The selected F1 progenies were further backcrossed to Ciherang 4 x to obtain BC5F1 progeny having 98% agronomic traits of those of Ciherang. In every cross/backcross generation, submergence test was performed, followed by sub1 marker-assisted PCR. F1 and BC1F1 submergence-tolerant Ciherang were successfully constructed. Co-dominant RM464A marker was not able to discriminate between host, donor, and progenies (F1 and BC1). Co-dominant RM219 maker showed slightly different size between donor and host amplicon, but it was difficult to see their heterozygous progenies. Both C173 and AEX1 dominant markers were able to show sub1 introgression from donor to host. PCR results confirmed that progenies-submergence tolerance was due to sub1 introgression, not escape mechanisms. AEX1 was chosen for subsequent experiments. Backcross until BC5 is in progress, to obtain maximum host retention for engineering new submergence tolerant varieties with good agronomic traits as those of Ciherang.